2018
DOI: 10.1111/jnc.14269
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of antiretroviral drugs on cultured primary astrocytes: analysis of neurotoxicity and matrix metalloproteinase inhibition

Abstract: There is little information available on the possible toxic effects that antiretroviral (ARV) drugs used for the treatment of human immunodeficiency virus (HIV)-infected subjects, may have on the central nervous system (CNS) resident cells. Moreover, it remains unclear whether the efficacy of the ARV drugs may also be due to their ability to exert extravirological effects on factors responsible for the development of HIV brain injury, e.g., matrix metalloproteinases (MMPs). This study investigates the toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…For example, neurotoxicity has been described for several viral proteins including gp120 and the transactivator of transcription (Tat) ( Table 1 ), as well as for host factors such as TNF-α, IL-1β, and IL-6 released from latently HIV-1-infected or -activated cells (Koller et al, 2001 ; Zhou et al, 2017 ). In addition, several ART drugs have been demonstrated to generate toxicity on their own (Brier et al, 2015 ; Underwood et al, 2015 ; Latronico et al, 2018 ). Thus, the combination of HIV-1-infection, low-level secretion of viral proteins, and ART toxicity probably contribute to CNS dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, neurotoxicity has been described for several viral proteins including gp120 and the transactivator of transcription (Tat) ( Table 1 ), as well as for host factors such as TNF-α, IL-1β, and IL-6 released from latently HIV-1-infected or -activated cells (Koller et al, 2001 ; Zhou et al, 2017 ). In addition, several ART drugs have been demonstrated to generate toxicity on their own (Brier et al, 2015 ; Underwood et al, 2015 ; Latronico et al, 2018 ). Thus, the combination of HIV-1-infection, low-level secretion of viral proteins, and ART toxicity probably contribute to CNS dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, growing interest has been focused in the last decade on the potential of drugs and natural compounds to inhibit MMPs. Numerous in vitro studies have evidenced that anti-inflammatory and antioxidant action of several drugs and bioactive compounds present in vegetables and marine organisms are associated with their abilities to inhibit the expression of MMPs (Latronico et al 2016(Latronico et al , 2018Di Bari et al 2015). In this study we demonstrated that among the tested ITCs, SFN and PEITC were the most effective in inhibiting MMP-2 and MMP-9 levels and expression in LPS-activated astrocytes.…”
Section: Discussionmentioning
confidence: 53%
“…The animals were euthanized by exposure to carbon dioxide (CO 2 ) and killed by rapid decapitation. The neocortical tissues were dissected and used for purification of primary glial cell cultures following the method reported by Latronico et al (2018). Briefly, after the dissection, rat brains were depleted of meninges and blood vessels, mechanical minced and digested with 0.25% trypsin in presence of 0.01% DNase.…”
Section: Preparation Of Astrocyte Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that exposure of astrocytes to Maraviroc, Raltegravir and Darunavir at high concentrations can lead to a reduction in MMP synthesis and activation. This effect was also shown to synergize when drugs were combined (Latronico et al 2018). Indinavir was demonstrated to inhibit the conversion of ProMMP2 into active MMP2 and decrease angiogenesis (Barillari et al 2014).…”
Section: Art-induced Bbb Dysfunctionmentioning
confidence: 98%